Comparison of the air pollution biomonitoring ability of three Tillandsia species and the lichen Ramalina celastri in Argentina - Bermudez, Gonzalo Miguel Angel (2009)
Bioaccumulation ability and response to air pollution sources were evaluated for Tillandsia capillaris Ruíz and Pav. f. capillaris, T. recurvata L., T. tricholepis Baker and the lichen Ramalina celastri (Spreng.)Krog. and Swinsc. Epiphyte samples collected from a non contaminated area in the province of Córdoba were transplanted to a control site and three areas categorised according to agricultural, urban and industrial (metallurgical and metal-mechanical) emission sources. Bioindicators were exposed for 3-, 6- and 9-month periods. A foliar damage index was established for Tillandsia and a pollution index for the lichen, and S, Fe, Mn and Zn concentrations were determined. An order of efficiency for the species and conditions studied is proposed taking into account heavy metal accumulation: T. recurvata > T. tricholepis >R. celastri >T. capillaris. All species studied showed Mn to be related to agricultural activity and Fe to industries and soil particles, and Zn was related to urban and industrial sources. As far as physiological response is concerned, T. tricholepis and T. capillaris were more sensitive to agricultural activities, whereas T. recurvata was sensitive to urban and industrial sources, and only partially to agricultural sources. No relationship was found for R. celastri.